Analisis Perdagangan Komoditas Perikanan Di Kecamatan Bantan Kabupaten Bengkalis (The Analysis of Trade on Fishery Commodity in Sub District Bantan, Bengkalis Regency) - Sri Endang Kornita; Yusbar Yusuf; Anthony Mayes (Jurnal Ekonomi, 2009)
The trade on fishery commodity need to examine the effectively for the fisher welfare.The objective of this research was to examine the trade of fisher in sub districtBantan, Bengkalis Regency, Riau Province. Primary data were collected throughfield research and 20 fishers had been deeply interviewed.Based on the result of research shown that trade, undoubtedly, had played animportant income in developing fisher establishments in Bantan. Comparative by thetrade have done by fisher at local and the cross island, to cross boundary; shown thetrade margin fr-omfisheryproducts are more better at the cross boundary trade, butfishfarmer sharefromfisheryproducts are more better at cross island trade.